International public administrations in global public policy sources and effects of bureaucratic influence - Knill, Christoph; Steinebach, Yves 1987- (Abingdon, Oxon, [England] Routledge, 2023)
"This book examines the rise and agency of International Organizations (IOs) and their bureaucratic bodies - the International Public Administrations (IPAs) - as a reflection of an ongoing transfer of political authority and power from the domestic to the international level. It shows that IPAs represent actors per se, with autonomy and resources that allow them to exert an independent influence on global policy-making processes and outputs. Providing a combination of novel conceptual lenses and research design to capture IPAs as an empirical phenomenon, the book takes an open, theoretically and methodologically diverse approach to show that IPAs are far from being negligible actors in global public policy and must be taken seriously as actors in policy-making beyond the nation state. This book will be of key interest to students, scholars and practitioners in Public Policy and Public Administration, International Relations, International Political Economy, as well as Organizational Studies"--
Chapter 1. Introduction : international public administrations in global public policy / Christoph Knill and Yves Steinebach

PART I: DIMENSIONS AND SOURCES OF IPA AUTHORITY: Chapter 2. No actorness without autonomy : researching IPAs' role in transnational policy-making / Michael W. Bauer and Jörn Ege -- Chapter 3. Conditions of influence : policy effects of IPA autonomy in comparative perspective / Michael W. Bauer, Jörn Ege, and Nora Wagner -- Chapter 4. Reputation and influence : a comparative assessment of stakeholder attitudes toward IPAs / Andrea Liese and Mirko Heinzel -- Chapter 5. Towards digital authority of international public administrations in global climate and disability policymaking / Alexandra Goritz, Helge Jörgens, Nina Kolleck, and Johannes Schuster.

PART 11: IPAs AS ORGANIZATIONS: Chapter 6. How administrative styles matter : international public administrations as agents in global public policy / Christoph Knill, Yves Steinebach, and Louisa Bayerlein -- Chapter 7. Bureaucratic agency and policy performance in international organizations / Yves Steinebach, Christoph Knill, Constantin Kaplaner, and Louisa Bayerlein -- Chapter 8. How administrative styles impact on organizational change and reforms of international public administrations / Stephan Grohs and Daniel Rasch.

PART III: RESOURCE POLITICS: Chapter 9. Money and time : budgeting and resourcing in international public administrations / Klaus H. Goetz, Ronny Patz, and Svanhildur Thorvaldsdottir -- Chapter 10. The politics of evaluation in international organizations / Steffen Eckhard and Vytautas Jankauskas.

PART IV: NODALITY: IPAs AS INTERFACE ACTORS: Chapter 11. Behind the scenes : how international treaty secretariats use social networks to exert influence in the global climate policy regime / Nina Kolleck, Helge Jörgens, Mareike Well, Barbara Saerbeck, Alexandra Goritz, and Johannes Schuster -- Chapter 12. Only words? : coordination and power in multilevel administration beyond the state / Arthur Benz -- Chapter 13. How and how much do international public administrations matter? : patterns and sources of their influence in global public policy / Christoph Knill and Yves Steinebach.
Includes bibliographical references and index.
Keywords: International agencies; Policy sciences -- International cooperation; Public administration -- International cooperation